2018
DOI: 10.1161/jaha.118.010584
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Valve Prolapse and Sudden Cardiac Death: A Systematic Review

Abstract: Background The relationship between mitral valve prolapse ( MVP ) and sudden cardiac death ( SCD ) remains controversial. In this systematic review, we evaluate the relationship between isolated MVP and SCD to better define a potential high‐risk subtype. In addition, we determine whether premortem parameters could predict SCD in patients with MVP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 79 publications
3
97
1
7
Order By: Relevance
“…Hui-Chen Han at al. indicated that electrophysiological changes include frequent ventricular premature complex on holter monitoring and ventricular fi brillation as the predominant cardiac arrest rhythm in mitral valve prolapse in a review (6).…”
Section: Discussionmentioning
confidence: 99%
“…Hui-Chen Han at al. indicated that electrophysiological changes include frequent ventricular premature complex on holter monitoring and ventricular fi brillation as the predominant cardiac arrest rhythm in mitral valve prolapse in a review (6).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients who had SCD had bileaflet involvement (70%) with redundant leaflets (99%), and majority did not have severe regurgitation (83%). Overall young females with redundant bileaflet prolapse had the highest risk of ventricular arrhythmias and SCD . A spiked configuration of the lateral annular velocities by echocardiography is also described as a marker of risk of SCD in MVP .…”
Section: Structural Abnormalitiesmentioning
confidence: 93%
“…The association of mitral valve prolapse (MVP) and SCD is not clear. Ventricular fibrillation was the major cause (81%) for sudden death in patients with mitral valve prolapse . Most of the patients who had SCD had bileaflet involvement (70%) with redundant leaflets (99%), and majority did not have severe regurgitation (83%).…”
Section: Structural Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This autonomic imbalance is hypothesized to be a crucial determinant at the beginning and also in progression of MVP. Autonomic dysregulation is an indicator of MVP pathogenesis and seems to be a very good predictor of miserable prognosis in MVP because of negative cases associated with congestive heart failure, progressive mitral insufficiency, thromboembolism, bacterial endocarditis, and even sudden cardiac death (2,17). These events, which appear at the terminal state in the course of aging, show up more frequently in patients with MVP (2).…”
Section: Sympathovagal Dynamic Balance -Functionmentioning
confidence: 99%